POLA PENERIMAAN MAHASISWA BARU BERBASIS SYARI’AH SEBAGAI RESPEK KONSISTENSI KE-ISLAMAN DAN KEBERAGAMAN DI UNIVERSITAS SUNAN GIRI SURABAYA - Ikhwanuddin, Ikhwanuddin; Farid, Muhammad; Syafi’i, Ahmad (Jurnal Kajian Hukum Islam, 2018)
Unsuri has a religious characteristic (culture aswaja), like a public campus characterized by “Islam". Characteristics like this, become one of the efforts to as well as a means to request support and cooperation with the community. Admittedly or not, Islamic education institutions or universities in several regions have until now felt that the community often dominated private universities, this was also felt by Unsuri, that most of the people around Unsuri did not immediately choose Unsuri as their chosen campus, based on this phenomenon, the author feels interested in knowing the initial state of the committee's strategy or the new Sunan Giri Surabaya student admission team, to find out the strategies and committee programs of Sunan Giri University Surabaya, this type of research is descriptive qualitative research, namely data collected in the form of words words, images, not numbers, according to Bagda and Taylor, as quoted by Lexy J. Moleong, qualitative research is a research procedure that produces descriptive data in the form of written or oral words from people and observed behavior. Meanwhile descriptive research is a form of research that is shown to describe or describe phenomena that exist both natural phenomena and human engineering